Structural Mediation Model of Information System and Sustainable Performance of UAE Manufacturing Sector - Ahmed Lari, Darwish; Ahmed Lari, Fatma; Darwish Abdulla Lari, Mohamed Ahmed (International Journal of Sustainable Construction Engineering and Technology, 2020)
This study intends to find out the mediating effect of organisational culture on the relationship between information system and sustainable performance of manufacturing sector in UAE. This study used AMOS-SEM software to develop mediation model that linking the mediating relationships between Information System, Organisational Culture and Sustainable operation Performance. Data was collected through questionnaire survey among the operation staff of Abu Dhabi manufacturing companies. A total 250 questionnaires were distributed however 205 were returned and only 200 are valid which indicates a response rate of 80%. The analysis found that TPS has positive but not significant effect to SP; OIS has positive but not significant effect to SP; FMW has a positive and significant effect on SP; SDS has a negative and not significant effect to SP and SP has positive but not significant effect OC. For the path relationship between the four exogenous variables (TPS, OIS, SDS, and FMW) and the mediator variable (OC), the results are TPS has positive and significant effect to OC; OIS has positive but not significant effect to OC; FMW has positive and significant effect to OC and SDS has positive and not significant effect to OC. Collectively, the five exogenous constructs (TPS, OIS, SDS, FMW and OC) explained 89% variation in operational performance and 86% of the variation in organisational culture. However, for a mediator, it was found that OC has no significant mediating effect on the relationship between TPS and SP; OC has no significant mediating effect on the relationship between OIS and SP; OC has no significant mediating effect on the relationship between SDS and SP and OC has no significant mediating effect on the relationship between FMW and SP. it can be concluded that there is a positive relationship between information system dimensions and operational performance. However organizational culture has no contributing any mediating effect to the relationship. These findings have contributed to the body of knowledge and could be shared among the UAE manufacturing practitioners